(untitled) (Fiep Bulletin - online, 2011)
The Body Mass Index is an indicator of the nutritional state based on the relationship of body mass and the height. When a bad relationship occurs, it should become a phenomenon that worries the health professionals, because of its association with cardiovascular diseases. The Sitting-Rising Test was idealized as a procedure to evaluate how people seats and rises from the ground. The association of Body Mass Index and the Sitting-Rising Test in adults indicates that the excess of body mass increases the difficulty in performing these motor actions. The aim of this paper was to make an overview about Body Mass Index of students of a basic school in Belford Roxo City (RJ) and to verify its relationship with the Sitting-Rising Test results of these children. The 284 students (164 male and 120 female) was evaluated about their body mass using an TBF-401 model bioimpedance scale device (Tanita – Japan) and about their height using an Cardiomed brand stadiometer (Brazil).It was used the International Obesity Task Force cutoff points for overweight and for obesity. The Sitting-Rising Test was conducted, according to the protocol developed by Araujo (1999), by a trained person. In order to verify the relationship between the variables, it was used the Spearman Correlation Coefficient. According to the Body Mass Index, the male volunteers was considered normal in 64,6%, over weighted in 25% and obese in 10,4% of the cases. To the female volunteers, it was found: normal = 66,7%, over weighted = 22,5% and obese = 10,8%. The Spearman Correlation Coefficient (r = - 0,62), the same value for both gender, suggests that body mass excess can influence, in a negative way, in the performance of fundamental motor actions.